“[Obeah] Ọbịa by Igbo Spelling” - Claudette A. Anderson (African Journal of Gender and Religion (AJGR))
Against the backdrop of the demonization of Africana Religious Traditions (ARTs), peoples of African descent, in shame and ignorance, and seduced by the benefits of a ruthless capitalist Christianity, fail to affirm the value of their ancestral spirituality. In Jamaica and other parts of the Anglophone Caribbean, the word “Obeah”, a label for African spirituality, remains misunderstood, demonized, and criminalized as Christians consistently thwart any effort to value it. Dibịa-Professor Umeh’s spiritual oeuvre provides necessary redress to the epistemicide that fuels the continued criminalization of “Obeah”. This article presents John Umeh’s After God is Dibịa: Igbo Cosmology, Divination & Sacred Science in Nigeria, Vols. 1 and 2 as performative texts that affirm traditional African Priesthood as honorable, valuable, and necessary, while negating the myth of a superior white male god and consequent female inferiority. I explore these acts of writing the Igbo Dibịahood as sacred performances of testimony, communion and redemption. The emphasis on Dibịa ethics, I posit as offering a critique of Christian priestcraft. African defined Ọbịa rejects eurocentric impositions on the term by affirming it as a healing vocation and inclusive priesthood defined by wisdom and knowledge. Through attention to the feminine space of revival, Ọbịa balmyard, I explore similarities with continental antecedents and present female Dibịahood as a radical faith tradition that insists on the power of Nne Agwu, Mother Holy Spirit. The respell of Ọbịa through eight emanations is shown as a potent antidote against epistemicide. By affirming the sacredness of matriarchal power, the dignity of traditional Dibịahood and the ethical force of traditional knowledge, Umeh exemplifies a priest class worthy of the name.